The kinetics of oxypropionic acid on natural zeolite - Gyvljud, Anna; Sabadash, Vira; Gumnitskij, Jaroslav (Lviv Polytechnic Publishing House, 2015)
This paper presents the results of experimental studies of the kinetics of ion exchange adsorption of lactic acid by zeolite in the periodic conditions. The results of experimental studies make it possible to determine the kinetic coefficients of the diffusion process.
Keywords: kinetic; zeolite; hydroksypropionic; wastewater; internal diffusion